The Impact of Age on Treatment Responses in Patients with Non-Small Cell Lung Cancer Treated with Immune Checkpoint Inhibitors - Alkan Şen, Gülin; Turna, Hande (Cerrahpaşa Medical Journal, 2024)
Objective: The correlation between age and the incidence and prevalence of cancer is well-established. Immunosenescence is thought to be underlying this condition. This retrospective research aimed to investigate the impact of aging on the responses to immune checkpoint inhibitor (ICIs) treatment responses in advanced non-small cell lung cancer (NSCLC) patients. Methods: Data was retrospectively collected from one cancer center. The treatment responses of advanced NSCLC patients treated with ICIs were compared between 2 groups based on age 65. Results: 30 patients were younger than 65 years old, and 20 patients were 65 years old or older. While the median progression-free survival (PFS) under 65 years of age was 21.6 months (95% CI: 5.2-38.0), in patients ≥ 65 years of age it was 13.5 months (95% CI: 3.3-23.7) (Hazard Ratio (HR) 1.31, 95% CI: 0.67-2.57, P = .423). For the median overall survival (OS), it was 27.8 months (95% CI: 20.6-34.9) in patients under 65 years of age, and 20.2 months (95% CI: 1.7-38.7) in patients ≥ 65 years of age (HR 1.18, 95% CI: 0.56-2.46, P = .651). There was also no significant difference in the objective response rate (ORR) between patients under 65 and ≥ 65 years of age, with rates of 43.3% and 25%, respectively (P = .186). Conclusion: Our study showed that age had no effect on ICIs responses in patients with advanced NSCLC. Prospective studies involving larger patient populations are required to evaluate the impact of age on ICIs responses. Cite this article as: Şen GA, Turna H. The impact of age on treatment responses in patients with non-small cell lung cancer treated with immune checkpoint inhibitors. Cerrahpaşa Med J. 2024;48(3):233-237.